Mieloma múltiplo: estudo prognóstico e verificação do conhecimento da doença em médicos que atuam na atenção primária à saúde - Roberta Oliveira de Paula e Silva (2007)
A nonconcurrent cohort study was carried out with the goal of identifyingclinical and laboratorial characteristics of patients suffering from Multipe Myeloma (MM) at the moment of diagnosis and correlating them with survival time. One hundred and one patients from the Outpatient Clinic for Lymphoproliferating Diseases at the Department of Hematology at UFMG University Hospital (Hospital das Clínicas da UFMG, HC-UFMG) who received the diagnosis of MM in the period between April 1994 and October 31 2006 were studied. Patients were followed-up until May 2007.The clinical knowledge of doctors working in the 137 Primary Health Care (PHC) units in Belo Horizonte about the disease was also assessed by means of a multiplechoice exam. Median patient age was 63 years, 47.5% were men and 52.5% were women, 50.6% having white skin, 33.3% black and 16.1% brown. Most common clinical manifestations were: bone pain (83.2%), weakness (70.3%) and weight loss (40.6%). Conventional bone radiograph showed alterations in 83.8% of the cases.Regarding the staging system proposed by Dürie & Salmon, 63 (62.4%) of patients were in stage III, 32 (31.7%) in stage II and only 6 (5.9%) in stage I at the moment of diagnosis. When the International Staging System (ISS) was used, 22 (30.1%) of patients were in stage III, 31 (42.5%) in stage II and 20 (27.4%) in stage I at the moment of diagnosis. Overall survival time was 66.52 months, with a follow-up median of 20 months. In multivariate analysis, parameters found to be significantwere: creatinin (p=0.006), hemoglobin (p=0.001), Dürie & Salmon staging (p=0.009) and ISS (p=0.014); and among these, only hemoglobin was correlated with survival time (P=0.012). In the exams for verifying the knowledge on MM, most doctors (94.1%) correctly concluded that an elderly patient with anemia should be evaluated for the presence of chronic and neoplasic diseases; 61.5% were unable to identifyMM as a diagnostic hypothesis for an elderly patient wit osteolysis in the X-ray and 60.7% could not diagnose hypercalcemia when presented with classical manifestations of this metabolic disorder. Most (71.1%) were unable to interpret seric protein electrophoresis and only 36.3% formulated the hypothesis of MM when faced with a characteristic clinical picture. None of these results were influenced by time since graduation, time working in PHC or the presence of medical specialty. It wasconcluded that most patients were in an advanced disease stage at the moment of diagnosis, which had a negative impact on survival time. Moreover, difficulties were observed in the recognition of clinical and laboratorial aspects of MM by doctors working in PHC.